2012
DOI: 10.1029/2011je003935
|View full text |Cite
|
Sign up to set email alerts
|

How old are young lunar craters?

Abstract: [1] The accurate definition of the lunar cratering chronology is important for deriving absolute model ages across the lunar surface and throughout the Solar System. Images from the Lunar Reconnaissance Orbiter Narrow Angle Cameras and Wide-Angle Camera and the SELENE/Kaguya Terrain Camera provide new opportunities to investigate crater size-frequency distributions (CSFDs) on individual geological units at lunar impact craters. We report new CSFD measurements for the Copernican-aged craters North Ray, Tycho, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
168
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(178 citation statements)
references
References 66 publications
7
168
3
Order By: Relevance
“…The errors on the ages reported in Table 1 are associated with inherent uncertainties in crater count chronologies (e.g., Hiesinger et al, 2012). The regression we present in the next section was calculated independently of these errors; however, to account for their potential influence, we calculated the 95% confidence belt on the regression (Fig.…”
Section: Crater Agesmentioning
confidence: 99%
“…The errors on the ages reported in Table 1 are associated with inherent uncertainties in crater count chronologies (e.g., Hiesinger et al, 2012). The regression we present in the next section was calculated independently of these errors; however, to account for their potential influence, we calculated the 95% confidence belt on the regression (Fig.…”
Section: Crater Agesmentioning
confidence: 99%
“…One of us (S. Marchi) did a test on the crater count of Marcia ejecta area 5a, and found that using a hard rock scaling law and a material strength of 4 Â 10 7 dyne/ cm 2 resulted in the same cratering model age as that found for the Marcia floor smooth unit, 60 Ma (that was derived using a strength of 2 Â 10 8 dyne/cm 2 , which is typical of hard rocks). Such variations in target properties between ejecta and impact melt, i.e., ejecta is composed of looser material than melted material, have been found to influence crater size-frequency distributions at small (61 km) crater sizes on the Moon (e.g., van der Bogert et al, 2010;van der Bogert et al, 2013a,b;Hiesinger et al, 2012). Other coauthors (TK, NS) suggest that the smooth unit on the elevated bench in the floor of Marcia crater is not a impact melt, but material emplaced during a resurfacing event between $25 Ma (resurfacing age in Marcia ejecta area 5b, closest to the crater wall) and 40 Ma (age of the smooth unit).…”
Section: Dark Diffuse Unit (Spotted Pattern Overlying Other Units)mentioning
confidence: 99%
“…Detailed physical arguments, models, numerical estimates and references can be found in the review paper itself. Jo Hermans, EPN Science Editor 2 The lunar crust is feldspar-rich, composed mainly of anorthite CaAl 2 Si 2 O 8 , with a density of ρ = 2.67 g cm -3 . 3 The mantle is composed mainly of olivines and pyroxenes (Mg,Fe)SiO 3 and (Mg,Fe) 2 SiO etc, with densities of ρ ≈ 3.5 g cm -3 and ρ ≈ 3.6 g cm -3 , respectively.…”
Section: The Giant Impactmentioning
confidence: 99%
“…Jo Hermans, EPN Science Editor 2 The lunar crust is feldspar-rich, composed mainly of anorthite CaAl 2 Si 2 O 8 , with a density of ρ = 2.67 g cm -3 . 3 The mantle is composed mainly of olivines and pyroxenes (Mg,Fe)SiO 3 and (Mg,Fe) 2 SiO etc, with densities of ρ ≈ 3.5 g cm -3 and ρ ≈ 3.6 g cm -3 , respectively. 4 Decay of 26 Al with a half-life of 0.7 Ma was the principal energy source for melting and differentiating asteroids very early in Solar-System history.…”
Section: The Giant Impactmentioning
confidence: 99%